Impact of Clostridioides difficile Infection on Clinical Outcomes in Hospitalized IBD Patients and the Role of Fecal Microbiota Transplantation: A Retrospective Cohort Study - Puo‐Hsien Le; Chyi‐Liang Chen; Chia‐Jung Kuo; Pai‐Jui Yeh; Chien‐Chang Chen; Yi‐Ching Chen; Cheng‐Tang Chiu; Hao‐Tsai Cheng; Yung‐Kuan Tsou; Yu‐Bin Pan; Cheng‐Hsun Chiu (Kaohsiung Journal of Medical Sciences)
ABSTRACT Clostridioides difficile infection (CDI) worsens the prognosis of patients with inflammatory bowel disease (IBD). This retrospective cohort study aimed to evaluate the risk factors, clinical manifestations, and outcomes of CDI in hospitalized patients with IBD, including those with toxin A/B results between April 2007 and April 2021. Patients were classified into the CDI and control groups. Patients with IBD and recurrent or refractory CDI underwent fecal microbiota transplantation (FMT). A total of 144 inpatients with IBD—45 in the CDI group and 99 in the control group—were analyzed. The incidence of CDI in inpatients with IBD was 31%. The Risk factors for CDI included longer IBD duration, biological therapy failure, and biological use. More patients in the CDI group presented with abdominal pain (77.8% vs. 55.6%, p = 0.011). In the antibiotic treatment‐only group, the symptom improvement rate was 60.7% (17/28), the microbiological cure rate was 89.3% (25/28), and the overall success rate was 71.4% (20/28). After antibiotic treatment and FMT, 71.4% (10/14) of the patients tested negative for CDI, and 64.3% (9/14) had improved clinical symptoms. CDI led to more hospitalizations (median two times [range 0–12] vs. median one time [range 0–19], p = 0.008), a lower steroid‐free remission rate (46.7% vs. 67.7%, p = 0.017), and higher Mayo scores (median 5 points [range 2–12] vs. median 3 points [range 0–12]). Patients who received FMT had fewer hospitalizations and fewer IBD‐related complications during follow‐up than those who received antibiotics alone. FMT should be considered in patients with IBD with refractory or recurrent CDI to improve clinical outcomes.